Towards post-democracy: shifting responsibilities and facilitating dispute resolution under the British neoliberal state - Lamsdale, S (2020)
This thesis investigates the State’s responsibility to facilitate dispute resolution and the extent to which this duty is upheld. This investigation is approached through Hobbesian social contract theory, which contends that the State must enable its citizens to resolve their conflicts through the public legal system. The primary function of the courts is to uphold the law, provide remedies for wrongs, and enforce rights. A central claim of this thesis is that citizens require lawyers to reach just outcomes. Most people, however, cannot afford lawyers. In the absence of affordable lawyers, this thesis asserts that the State must provide access to lawyers through legal aid to uphold its duty to facilitate dispute resolution. Providing legal aid, however, increases the State’s costs. Using political theory, this dissertation considers how rising costs conflict with the State’s neoliberal ideology. It argues that, to reduce costs, the British neoliberal State has diminished its role in facilitating dispute resolution by restricting the availability of legal aid and has sought to shift its responsibility onto charities, volunteers, and the private dispute resolution sector. Doing so reduces people’s ability to resolve their disputes within the public courts justly. This dissertation then explores the consequences that this has for democracy. By enabling people to hold the State accountable and using dispute resolution to lead to developments of the law, litigation provides a way for people to engage in self-government. This thesis contends that, in undermining people’s ability to resolve their disputes through the public courts, the State’s attempts to shift its responsibility of facilitating dispute resolution pushes society towards ‘post-democracy’. Post-democracy is a situation where society maintains the façade of democracy, but its democratic institutions are hollowed out of their substantive value.